Kinetics of homomeric GluR6 glutamate receptor channels. - Heckmann, M (1996)
We studied the kinetics of the unedited version of rat GluR6 glutamate (glu) receptor channels, GluR6Q, in outside-out patches using a system for submillisecond solution exchange. Half-maximum activation of the channels was reached with approximately 0.5 microM glu. The maximum slope of the double-logarithmic plot of the peak current versus glu was approximately 1.3, indicating that at least two binding steps are necessary to open the channels. Currents in response to a pulse of 10 microM glu had a short rise time (10-90% of peak current) of approximately 220 microseconds at approximately 20 degrees C. The rise time increased with falling glu concentration, reaching approximately 6.0 ms with 10 microM glu. In the continued presence of glu, the channels desensitized, and this desensitization can be described with a single time constant of approximately 7.0 ms for a pulse of 10 microM glu. The steady-state current in response to a long pulse of 10 microM glu was below 1/280th of the peak current. The time constant of desensitization was found to be independent of concentration between 30.0 and 0.3 microM glu, but to be increased for lower concentrations. After a short pulse of 1 ms duration and 10 or 0.3 microM glu, currents decayed with a time constant of approximately 2.5 ms. Recovery from desensitization after a pulse took approximately 5 s, and the half-time of recovery was approximately 2.2 s. Continuous application of low concentrations of glutamate reduced the peak currents in response to a pulse of 10 microM glu markedly. Fifty percent response reduction was observed in the continuous presence of approximately 0.3 microM glu. Our results for homomeric GluR6 agree with a cyclical reaction scheme developed for completely desensitizing, glu-activated channels on crayfish muscles.